Analysis of the Ibotenic Acid, Muscimol, and Ergosterol Content of an Amanita Muscaria Hydroalcoholic Extract with an Evaluation of Its Cytotoxic Effect against a Panel of Lung Cell Lines In Vitro - Dushkov, Alexander; Vosáhlová, Zuzana; Tzintzarov, Alexander; Kalíková, Květa; Křížek, Tomáš; Ugrinova, Iva (Molecules (Basel, Switzerland), 2023)
The fungus Amanita muscaria is universally recognizable for its iconic appearance; it is also widely regarded as poisonous, inedible, and even deadly. In spite of that, there have been documented cases of use of A. muscaria-containing preparations against various diseases, including cancer, to no apparent ill effect. The search for compounds that can be used to treat cancer among various plants and fungi has been intensifying in recent years. In light of this, we describe an HPLC HILIC analytical method for the evaluation of the content of the anticancer compound ergosterol (ERG) and the neuroactive alkaloids ibotenic acid (IBO) and muscimol (MUS) that contribute significantly to the unpleasant physiological syndrome associated with A. muscaria consumption. A 'homemade' A. muscaria tincture made using 80-proof rye vodka as the solvent, an A. muscaria extract made with a standardized water-ethanol solution as the solvent, and fractions obtained from the second extract via liquid-liquid extraction with nonpolar solvents were analyzed. The study also presents the results of capillary zone electrophoresis with contactless conductivity detection and UHPLC-MS/MS analyses of the IBO and MUS content of the two native A. muscaria extracts and an evaluation of the standardized extract's cytotoxic effect against a small panel of lung cell cultures in vitro. Our results show that the standardized extract has a significant cytotoxic effect and does not contain the compounds of interest in any significant quantity.
Keywords: Muscimol; Plant Extracts; Solvents; kyselina ibotenová; buněčné linie; Humans; rozpouštědla; capillary electrophoresis; Antineoplastic Agents; lidé; cancer; alkaloids; nádory; tandemová hmotnostní spektrometrie; fungi; Lung; rostlinné extrakty; Amanita; muscimol; cytotoxicity; Cell Line; Tandem Mass Spectrometry; Ibotenic Acid; Neoplasms; plíce; protinádorové látky; HPLC; mass spectrometry; Amanita muscaria